Influence of speed on the internal flow characteristics of a multiphase pump based on a coupled CFD-PBM model - Guo, Xin; Shi, Guangtai; Chai, Hongqiang; Lv, Wenjuan; Fu, Jie (Frontiers in Physics, 2024)
Under the influence of the characteristic behavior of the bubbles, the flow pattern in the multiphase pump suffers a serious deterioration and the pressurization performance is significantly reduced. In order to be more close to the engineering practice, the CFD-PBM (Computational Fluid Dynamics-Population Balance Model) coupling model is established and verified on the basis of considering the bubble coalescence and breakup behavior, revealing the bubble distribution characteristics in the pressurization unit, and studying the influence of speed on the internal flow characteristics of the multiphase pump. The results show that the volume fraction of large bubbles in the pressurization unit of the multiphase pump decreases significantly with increasing speed, and the bubble coalescence zone shrinks parallel to the blade profile along the flow direction. The volume fraction of small bubbles increases sharply with speed, and the bubble breakup zone covers almost the entire fluid domain at high speed conditions. The speed has a significantly greater influence on the distribution of the gas phase and the vortex structure in the diffuser domain than in the impeller domain. In the diffuser domain, a pair of mutually separate vortices are formed, and a large number of gas phases are sucked near the vortex center. With the increase of speed, the velocity slip in impeller domain is weakened, but in diffuser domain is intensified. The results of the study can accurately predict the performance variation of the multiphase pump and are important for their optimal design and engineering application.